Dr. Buzby’s ToeGrips® Application Results in Minimal Changes in Kinetic Gait Parameters in Normal Dogs - Roush, James K.; Moore, Leslie E.; Renberg, Walter C. (Frontiers in Veterinary Science, 2017)
Poor traction on slick surfaces is difficult for dogs with neurologic deficits, osteoarthritis or recovering from injury or surgery. Many dogs respond inappropriately to slick surfaces by decreasing digital pad-floor contact and extending their toenails. A device marketed to increase paw-floor friction in dogs was evaluated. Fifteen normal dogs underwent kinetic gait analysis before and after application of Dr. Buzby’s ToeGrips®. Ground reaction forces, including vertical peak force and impulse for each limb were measured and compared between pre- and post-application values. Stance time was significantly increased in all limbs after toe grip application. Stride velocity was slower in all limbs, but significantly slower only in the left forelimb. Vertical peak force was significantly deceased in both hindlimbs after toe grip application but the decrease was within the group standard deviations. Vertical impulse was significantly increased in both forelimbs and in the right hindlimb. Dr. Buzby’s ToeGrips® result in a slower gait, with slightly decreased vertical peak force in the hindlimbs and increased effort for propulsion Kinetic changes were of minor magnitude and unlikely to be clinically relevant.